Interactions, mergers and the fundamental mass relations of galaxies - Tissera, Patricia Beatriz (2006)
We present a study of the effects of mergers and interactions on the mass distribution of galactic systems in hierarchical clustering scenarios using the disc-bulge structural parameters and their dynamical properties to quantify them. We focus on the analysis of the Fundamental Mass Plane relation, finding that secular evolution phases contribute significantly to the determination of a plane with a slope in agreement to that of the observed luminosity relation. In these simulations, secular phases are responsible for the formation of compact stellar bulges with the correct structural parameter combination. We also test that the relations among these parameters agree with observations. The Kormendy mass relation is also reproduced after secular evolution phases. From our findings, we predict that the departure of systems from the z=0 Fundamental Mass Plane, involving a change in the slope, could indicate a lack of secular evolution in their formation histories. Taking into account these results, the hierarchical growth of the structure predicts a bulge formation scenario for typical field spiral galaxies where secular evolution during dissipate mergers plays a fundamental role. Conversely, subsequent mergers can help to enlarge the bulges but do not seem to strongly modify their fundamental mass relations. Systems get to the local mass relations at different stages of evolution (i.e. different redshifts) so that their formation histories introduce a natural scatter in the relations. We also found that the parameters of the Tully-Fisher Mass relation for the disc components are correlated with those of the Fundamental mass one for the bulge components at least during mergers events, so that as the systems increase their circular velocity, the bulges get more concentrated. Our results suggest that the formation mechanisms of the bulge and disc components, satisfying their corresponding fundamental mass relations, might be coupled and that secular evolution could be the possible connecting process.